2014
DOI: 10.1158/2159-8290.cd-13-0633
|View full text |Cite
|
Sign up to set email alerts
|

CD74–NRG1 Fusions in Lung Adenocarcinoma

Abstract: We discovered a novel somatic gene fusion, CD74-NRG1 , by transcriptome sequencing of 25 lung adenocarcinomas of never smokers. By screening 102 lung adenocarcinomas negative for known oncogenic alterations, we found four additional fusion-positive tumors, all of which were of the invasive mucinous subtype. Mechanistically, CD74-NRG1 leads to extracellular expression of the EGF-like domain of NRG1 III-β3, thereby providing the ligand for ERBB2-ERBB3 receptor complexes. Accordingly, ERBB2 and ERBB3 expression w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
250
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 240 publications
(261 citation statements)
references
References 21 publications
8
250
2
1
Order By: Relevance
“…Furthermore, NRG1 fusion-mediated signaling could be suppressed by clinically approved kinase inhibitors (35). NRG1 fusions are preferentially found in women who had never smoked, and whose tumors are negative for other known mutant oncogenic gene mutations such as those in KRAS [frequently mutated in invasive mucinous adenocarcinoma (IMA)], or EGFR (34,35). In another study, CD74-NRG1-positive tumors displayed uncommon radiologic features in comparison with what it is usually seen in IMA (36).…”
Section: Erbb1 (Egfr; Ref 1) Erbb2 (Her2; Ref 2) Erbb3mentioning
confidence: 98%
See 3 more Smart Citations
“…Furthermore, NRG1 fusion-mediated signaling could be suppressed by clinically approved kinase inhibitors (35). NRG1 fusions are preferentially found in women who had never smoked, and whose tumors are negative for other known mutant oncogenic gene mutations such as those in KRAS [frequently mutated in invasive mucinous adenocarcinoma (IMA)], or EGFR (34,35). In another study, CD74-NRG1-positive tumors displayed uncommon radiologic features in comparison with what it is usually seen in IMA (36).…”
Section: Erbb1 (Egfr; Ref 1) Erbb2 (Her2; Ref 2) Erbb3mentioning
confidence: 98%
“…Finally, analyses of prostate cancer cells and tumors suggest the existence of a paracrine loop involving NRG1 and the ERBB2-ERBB3 heterodimer (33). We recently discovered recurrent CD74-NRG1 gene fusions, which result in the expression of the NRG1 III-b3 isoform in the otherwise NRG1-negative invasive mucinous subtype of lung adenocarcinomas (34). CD74-NRG1 activates ERBB3 as well as PI3K-AKT signaling (34), thus promoting anchorage-independent growth of NIH-3T3 cells (ref.…”
Section: Erbb1 (Egfr; Ref 1) Erbb2 (Her2; Ref 2) Erbb3mentioning
confidence: 99%
See 2 more Smart Citations
“…With pathological findings proving more valuable than nonaddictive molecular biomarkers (KRAS, MSH2 and TUBB3) for choosing the optimal treatment, our data confirmed that chemotherapy should be preferred over EGFR-TKIs for patients with mucinous L-ADC. However, several novel somatic gene fusions could represent a therapeutic opportunity for advanced mucinous L-ADC, a tumour for which no effective treatment exists, except chemotherapy, and which frequently presents with multifocal unresectable disease [43,44].…”
Section: Discussionmentioning
confidence: 99%